The Elusive Endometrial Epithelial Stem/Progenitor Cells - Cousins, Fiona L.; Pandoy, Ronald; Jin, Shiying; Gargett, Caroline E. (Frontiers in Cell and Developmental Biology, 2021)
The human endometrium undergoes approximately 450 cycles of proliferation, differentiation, shedding and regeneration over a woman’s reproductive lifetime. The regenerative capacity of the endometrium is attributed to stem/progenitor cells residing in the basalis layer of the tissue. Mesenchymal stem cells have been extensively studied in the endometrium, whereas endometrial epithelial stem/progenitor cells have remained more elusive. This review details the discovery of human and mouse endometrial epithelial stem/progenitor cells. It highlights recent significant developments identifying putative markers of these epithelial stem/progenitor cells that reveal their in vivo identity, location in both human and mouse endometrium, raising common but also different viewpoints. The review also outlines the techniques used to identify epithelial stem/progenitor cells, specifically in vitro functional assays and in vivo lineage tracing. We will also discuss their known interactions and hierarchy and known roles in endometrial dynamics across the menstrual or estrous cycle including re-epithelialization at menses and regeneration of the tissue during the proliferative phase. We also detail their potential role in endometrial proliferative disorders such as endometriosis.